Pengaruh Minat Belajar Dan Pemahaman Kalimat Terhadap Kemampuan Menulis Kalimat Efektif - Sigit Widiyarto (Universitas Mathla'ul Anwar Banten, 2017)
This study aimed to get an idea of the effect of Interest in Learning and pemahanan sentence to sentence effective writing skills junior high school students of SMP Al-Ikhlas Kayuringin Bekasi .The effect Comprehension Writing Skills sentence toThe ability to write Effective sentence and influence skills Interest in Learning to write effective sentence. This study uses the 35 sampel. Kuantitatif technique.Sampel data retrieval using Simple Random Sampling. The result based research can be concluded: 1) Interest in Learning does not affect the sentence effective writing skills. 2) Understanding Sentence significant effect on the ability to write sentences efektif.3) .Interest in Learning and Understanding sentence jointly influence significantly the ability to write effective sentence.